2021
DOI: 10.3390/molecules26061762
|View full text |Cite
|
Sign up to set email alerts
|

Eudesmane and Eremophilane Sesquiterpenes from the Fruits of Alpinia oxyphylla with Protective Effects against Oxidative Stress in Adipose-Derived Mesenchymal Stem Cells

Abstract: Alpinia oxyphylla Miquel (Zingiberaceae) has been reported to show antioxidant, anti-inflammatory, and neuroprotective effects. In this study, two new eudesmane sesquiterpenes, 7α-hydroperoxy eudesma-3,11-diene-2-one (1) and 7β-hydroperoxy eudesma-3,11-diene-2-one (2), and a new eremophilane sesquiterpene, 3α-hydroxynootkatone (3), were isolated from the MeOH extract of dried fruits of A. oxyphylla along with eleven known sesquiterpenes (4–14). The structures were elucidated by the analysis of 1D/2D NMR, high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…22,25,32 This compound inhibited LPS-induced NO production and protected against oxidative stress-induced adipose-derived mesenchymal stem cells. 33,34 A possible mechanism of action has not been proposed. In the present study, Western blotting and molecular docking indicated that compound 12 exerted anti-neuroinflammatory activity probably via regulation of TLR-4/NF-κB signaling, and so it has the potential to be developed as a possible therapeutic agent to treat NDDs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,25,32 This compound inhibited LPS-induced NO production and protected against oxidative stress-induced adipose-derived mesenchymal stem cells. 33,34 A possible mechanism of action has not been proposed. In the present study, Western blotting and molecular docking indicated that compound 12 exerted anti-neuroinflammatory activity probably via regulation of TLR-4/NF-κB signaling, and so it has the potential to be developed as a possible therapeutic agent to treat NDDs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compared with LPS-treated cells, preincubation with 12 suppressed LPS-induced expression of TLR-4, iNOS, and cyclooxygenase-2 (COX-2) and reduced the p-NF-κB/NF-κB ratio (Figure ). Compound 12 was previously reported in phytochemical studies on grapefruit juice and the fruits of Alpinia oxyphylla . ,, This compound inhibited LPS-induced NO production and protected against oxidative stress-induced adipose-derived mesenchymal stem cells. , A possible mechanism of action has not been proposed. In the present study, Western blotting and molecular docking indicated that compound 12 exerted anti-neuroinflammatory activity probably via regulation of TLR-4/NF-κB signaling, and so it has the potential to be developed as a possible therapeutic agent to treat NDDs.…”
Section: Resultsmentioning
confidence: 99%
“…2 Additionally, the dried fruits of A. oxyphylla have been traditionally used as a Chinese medicine and are recorded in the Pharmacopoeia of the People's Republic of China for their tonic, aphrodisiac, and anti-polyuria effects. 3 Previous phytochemical studies have identified various compounds in A. oxyphylla, including volatile oil, 4 terpenes, 5 diarylheptanes 6 and flavonoids. 6 Among these constituents, sesquiterpenoids are considered the characteristic and main bioactive constituents.…”
Section: Introductionmentioning
confidence: 99%
“…15 As part of our ongoing investigation of more novel effective anti-inflammatory sesquiterpenoids from A. oxyphylla, a total of 38 structurally diverse sesquiterpenoids (Fig. 1), including six previously undescribed eremophilane sesquiterpenoids (1)(2)(3)(4)(5)(6), six new cadinane sesquiterpenoids (23)(24)(26)(27)(28)(29), and 26 known analogues (7-22, 25 and 31-38) were isolated and identified. Among the isolates, compound 1 possesses an unusual rearranged eremophilane skeleton, 28 and 29 are unusual rearranged cadinane sesquiterpenoids, featuring rare spiro [5.6] carbon skeletons, while 23, 24, 26, and 27 are rare nor-cadinane sesquiterpenoids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation